Construção de tesauros e análise de domínio: perspectivas conceituais, teóricas e metodológicas a partir das influências étnicas nos léxicos - Morais, Natanna Santana de (2024)
Thesauri are knowledge organization systems (Knowledge Organization System - KOS) widely used for information representation and retrieval purposes. However, it is believed that these systems are faced with problems relating to instability in communication processes, lexical dispersions in addition to other issues involving inadequacy in the processing of information and the non-introduction of terms originating from lexicons that inherited ethnic influences. Other impasses arise from the emphasis given to hegemonic epistemological aspects (scientific, sexist and racist elites) that prioritize methodologies and standards, making the construction of thesauruses unfeasible in the Brazilian scenario of ethnic-racial diversity. Given this scenario, Domain Analysis was introduced as a social paradigm and integrator of methodologies and theoretical aspects to discover and explore domains, aiming to develop studies in Information Science and knowledge organization systems. In particular, the “production of special classifications and thesauruses” is one of the eleven approaches to Domain Analysis. From this perspective, this research seeks to answer the following problem: How does national and international research in Domain Analysis and construction of Thesauruses contribute to and or diverge conceptually, theoretically and methodologically from ethnic-racial and cultural issues raised from ethnic influences in the lexicon of Portuguese spoken in Brazil? In this sense, the research has as its general objective: analyze the possible contributions, divergences and/or theoretical, conceptual and methodological approaches between the construction of thesauruses, Domain Analysis and lexical studies based on Brazilian ethnic influences, considering research at national and international levels. Thus, basic concepts were highlighted: ethnicity, race, racism and nation. Methodology: This is a Correlational and documentary research whose survey took place in the Information Science Database (BRAPCI); in the Scielo Citation Index Collection of the Web of Science and in the Library, Information Science & Technology Abstracts (LISTA). The framework drew on the history of lexical studies and attested to the extinction of the majority of indigenous and Afro-Brazilian languages. The methodological procedures were conducted according to the quantitative-qualitative approach and content analysis. Results: the research corpus identified 139 documents, including articles and book chapters. Conclusion: Based on the readings and inferences, theories, paradigms, approaches, methods, analyzes and methodological proposals were viewed as points of convergence, divergence and approximation between Domain Analysis, the theoretical and practical foundation of thesauruses and the perspectives of studies of lexicons in scientific and non-scientific domains. Among the conceptual aspects, the concepts and issues of gender and sexual diversity, literary and cultural guarantees, ethnoknowledge, cultural hospitality and intersectionality stood out, in addition to the implications regarding the coloniality of power and social classification. The theoretical contributions linked to thesauri and domain studies emphasized: Concept and Faceted Classification Theories, epistemological theories and knowledge perspectives (Empiricism, Positivism, Rationalism, Realism, Pragmatism, Hermeneutics and Historicism). Bibliometric analyzes and methodological proposals focused on lexicons appeared as viable possibilities in the development of thesauruses in different domains.